Pengaruh Project Based Learning Berbasis Blended Learning Menggunakan Edmodo Terhadap Hasil Belajar Peserta Didik pada Mata Pelajaran Biologi di SMAN 1 Lareh Sago Halaban. - Jazuli, Dini Aulia Rahmi; Zakir, Supratman (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2022)
This research is motivated by the lack of enthusiasm and student response to the material presented by the teacher in class which is a form of discomfort and the lack of feedback from students to the teacher will greatly affect student learning outcomes, especially during the current pandemic. Learning methods are needed that can involve students more in learning so that students become interested and not easily bored in participating in Biology lessons and one solution is to apply the Project Based Learning learning model based on Blended Learning using Emodo which will be integrated with 20th century abilities. 21 (critical thinking skills, creative thinking, communication and collaboration). The type of research used is quantitative with a correlational approach. The population of this study were all students of class X IPA SMA N 1 Lareh Sago Halaban. Sampling using Simple Random Sampling. Determination of the number of samples using the Slovin formula. The sample in this study was 88 students with the chosen sampling method was cluster sampling. The sample was selected using a lottery technique, namely taking a small roll of paper with the student's name on it. The type of questionnaireused in this study is a direct questionnaire, which is in the form of a Likert scale. Based on the results of research data analysis, it can be concluded that Project-Based Learning based on Blended Learning using Edmodo contributes 99.7% to learning outcomes while the remaining 0.3% is explained by other variables not included in the regression model. The correlation test analysis shows that Project Based Learning Based on Blended Learnin Using Edmodo has an effect on student learning outcomes in Biology Subjects at SMA N 1 Lareh Sago Halaban with a correlation value of 0.999 with p<α (0.000).